Content Moderation: How the EU and the U.S. Approach Striking a Balance Between Protecting Free Speech and Protecting Public Interest (Trento Student Law Review, 2023)
The topic of content moderation is becoming increasingly relevant, as we are in an era of acute politicization and social media are now used to achieve political goals. This means that regulation is necessary to preserve democratic standards and simultaneously encourage a healthy online environment. This article aims at analyzing and comparing how content sharing is regulated respectively in the EU and U.S. and at identifying the benefits and shortcomings of both methods. It does so by using information from government agencies, social media companies, and specific cases which reflect the policies in both regions. It is evident that while both the U.S. and the EU have taken steps to regulate online content, there are significant differences. The EU chooses a more centralized approach and values the protection of users and public interest, whilst the U.S. adopts a more decentralized approach and tends to opt for the protection of free speech. Lack of transparency, over-removal, under-removal, and vague social media standards are the difficulties that both the EU and the U.S. face in regulating online content. This article recommends potential answers to these problems, including regulating platform transparency, increasing accountability, and establishing oversight bodies. Moreover, platforms are encouraged to invest in their content moderation policies by using higher-level means of finding and removing harmful content.
Keywords: content moderation; Internet governance; censorship; Section 230; Digital Services Act